Comparison of PIC and SIC with Lattice Reduction cancellation schemes for V-BLAST MIMO system - Evgeny Goncharov (IAES Indonesia Section, 2019)
This paper discusses the design of the MIMO signal demodulation algorithm built according to the V-BLAST scheme. Several algorithms such as the maximum likelihood algorithm and QR-M algorithm, Minimum of Mean Square Error (MMSE), Successive Interference Cancellation (SIC) with MMSE (SICMMSE), Parallel Interference Cancellation (PIC) with MMSE (PIC-MMSE), Lattice Reduction MMSE (LR-MMSE), as well as modifications of SIC-LR-MMSE, PIC-LR-MMSE are considered. It is shown that the SIC-LR-MMSE and PIC-LR-MMSE algorithms, presented in this paper, having a linear computational complexity depending on the number of antennas and modulation order, provides good performance close to potentially achievable (MLA), which makes its practical use possible. The presented algorithm can be used to improve performance of CDN (Content Delivery Networks) or CMS (Content Management Systems) to transmit content in different distributed content delivery systems.